PENERAPAN METODE KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN PRESTASI BELAJAR PADA MATA PELAJARAN SISTEM KOPLING SISWA KELAS XI TKR SMK NEGERI 2 KALIANDA LAMPUNG SELATAN - Nenden Tiara Ardani; Setuju Setuju (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this study is to determine whether the application of the cooperative learning method type STAD (Student Team Acvhievement Division) can improve learning achievement clutch system subjects in student of class XI TKR expertaise at Kalianda 2 Vocational Hight School of South Lampung. The study hypothesis cooperative learning methods type STAD (Student Team Acvhievement Division) can Improving learning achievement cluth system subject in students of class XI TKR Kalianda 2 Vocational Hight School of South Lampung.This research was conducted in Kalianda 2 Vocational Hight School on May 10 until June 10. This type of research is a classroom action research (CAR). The research subjects is students of class XI TKR totaling 32 students. The research object is cooperative learning methods type STAD (Student Team Acvhievement Division) Improving learning achievement cluth system subject. Data collection techniques with engineering tests, observation sheets, and documentation. Qualitative and quantitative approaches with 3 cycles. Each cycle consists of planning, implementation (interview, observation, documentation, and testing), observation and reflection. The validity of the formula obtained by product moment correlation. Reliability was obtained by the formula alpha cronbacht.The study found the following results: (1) cooperative learning methods type STAD (Student Team Acvhievement Division) can Improving learning achievement cluth system subject in students of class XI TKR Kalianda 2 Vocational Hight School of South Lampung.. Student achievement in pre-test of 48.12 is increased in the post-test first cycle to 60.78, then increased in the post-test cycle II to 70.31 and the last increase in the third cycle into 80.78. (2) The effect that occurs in the process of implementation of learning with using cooperative learning methods of type student Team Achievement Division (STAD) may increase the activity student of class XI TKR Kalianda 2 Vocational Hight School of South Lampung. Activity of students in the first cycle of 37.50% positive increase in the second cycle of 58.81% and no third cycle increased to 82.03%.